The Ancient Abu Al-Khaseeb River, Origin and Extinction - By Geophysical Investigations - Al-Mosawi, Walaa; AL- Muturi, Zainab; Almayahi, Dawod (Mesopotamian Journal of Marine Sciences, 2025)
In Basrah Governorate, south of Iraq, there are many ancient river course sites. This issue is related to the nature of the region that represents the lower part of the Mesopotamian basin. One of these courses is the ancient Abu Al-Khaseeb River course; many queries have been raised about its existence, location, origin, and extinction, which is the subject of the current study. The current study uses Ground Penetration Radar and Sub Bottom profiler surveys to determine the trace of a river course named (the old Abu Al-Khaseeb River) extending from the main road that links the center of Basrah city with Al-Faw city and extends for 31.65 km towards the west at one of the dendrite branches of Khor Al-Zubair channel. The average width of this stream is about 40 m, and its depth does not exceed 2 m. The straightness of this course and its extension from east to west, unlike the river courses in the region (from north to south), the extent of ancient irrigation systems on both sides of this captured course, and the flatness of the land along it, all these features are evidence that this river course was the artificial origin for irrigation or drainage purposes for the area which was agriculturally active in the Abbasid period, according to historical sources